2014
DOI: 10.1517/17425247.2014.941355
|View full text |Cite
|
Sign up to set email alerts
|

Coacervate delivery systems for proteins and small molecule drugs

Abstract: Coacervates represent an exciting new class of drug delivery vehicles, developed in the past decade as carriers of small molecule drugs and proteins. This review summarizes several well-described coacervate systems, including Elastin-like peptides for delivery of anti-cancer therapeutics,Heparin-based coacervates with synthetic polycations for controlled growth factor delivery,Carboxymethyl chitosan aggregates for oral drug delivery,Mussel adhesive protein and hyaluronic acid coacervates. Coacervates present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 29 publications
1
100
0
Order By: Relevance
“…The coacervate contains heparin and a biocompatible polycation, PEAD, which closely and advantageously imitates the native signaling environment involving extracellular matrix proteoglycans, ligands, and cell receptors [33, 5557]. This vehicle can protect the GFs from rapid enzymatic degradation and potentiate their bioactivities [24, 25, 2733]. In this study, we demonstrated that the fibrin gel-coacervate system achieved early release of VEGF to trigger EC proliferation and sprouting and delayed release of PDGF to recruit pericytes that stabilize the newly formed vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The coacervate contains heparin and a biocompatible polycation, PEAD, which closely and advantageously imitates the native signaling environment involving extracellular matrix proteoglycans, ligands, and cell receptors [33, 5557]. This vehicle can protect the GFs from rapid enzymatic degradation and potentiate their bioactivities [24, 25, 2733]. In this study, we demonstrated that the fibrin gel-coacervate system achieved early release of VEGF to trigger EC proliferation and sprouting and delayed release of PDGF to recruit pericytes that stabilize the newly formed vessels.…”
Section: Discussionmentioning
confidence: 99%
“…73, 74 Although the complex coacervate is also an important drug delivery system for biomedical applications, it will not be included in this review and readers can refer to several recent publications for their interesting applications. 75, 95100 To use a synthetic polyelectrolyte to form a hydrogel, an ABA triblock copolymer architecture is used. 78, 101 Fig.…”
Section: Ionic Interaction-based Hydrogelsmentioning
confidence: 99%
“…phase separation | elastin | NMR | protein structure | dynamics T he liquid-liquid phase separation (LLPS) of molecules has long been exploited to concentrate and encapsulate molecules for drug delivery and food preparation (1,2). In biology, there is increasing awareness that many proteins exhibit this type of phase behavior, allowing transient microenvironments to be quickly assembled and disassembled in response to changing solution conditions, or the availability of binding partners (3,4).…”
mentioning
confidence: 99%